Leadership style and school culture as perceived by teachers in Malaysian Northern State schools - Amzat, Ismail Hussein (IGI Global, 2019)
This chapter explores the effective leadership style for positive school culture as perceived by some Malaysian Northern State school teachers. This chapter uses focus group and open-ended questions to have in-depth understanding and testing of the participants' ability of suggesting or predicting the best or most effective school leadership style for building school positive culture for best leadership practices. The participants were teachers from different schools in Northern States Malaysia undertaking master program in educational management at Universiti Utara Malaysia. The findings revealed that transformational leadership style was rated, predicted, and ranked as the best leadership style for school principals to apply in building positive school culture according to their context while distributed leadership and instructional leadership could be also considered as the second leadership styles for building positive school culture in the Northern schools of Malaysia.